A Rare Case of Transverse Sinus Venous Thrombosis Simulating Postdural Puncture Headache After Cervical Epidural Injection. Issue 3 (1st August 2016) - Guirguis, Maged; Jusino, Eduardo; Tolba, Reda; Samuel, Samuel
Abstract : Postdural puncture headache (PDPH) is a feared complication related to epidural steroid injections. We report a unique case in which all subjective and objective findings indicated the diagnosis of PDPH. However, the patient failed appropriate conservative and interventional management. Therapeutic failure prompted further investigation to establish the correct diagnosis of cerebral venous sinus thrombosis. Cerebral venous sinus thrombosis is a rare, difficult to diagnose, but potentially lethal disorder with nonspecific and variable clinical presentations, including headache and focal neurological deficits. Performing magnetic resonance imaging and magnetic resonance venogram should be considered early, especially in patients who fail to respond to standard interventions for PDPH.